Role of selective progesterone receptor modulators in the treatment of symptomatic uterine fibroids - Naresh, Neha; Mani, Poonam; Yadav, Lalita; Singh, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Uterine leiomyomas are benign tumours of smooth muscle cells and fibrous tissue that develop within the wall of the uterus. Objective of this study was to compare efficacy and safety of Mifepristone and Ulipristal acetate in the treatment of symptomatic uterine fibroids. Methods: The present randomized comparative prospective study was conducted among 120 non-pregnant and non-lactating females of age 25-50 years with symptomatic fibroids reported in the department of obstetrics and gynecology, Chhatrapati Shivaji Subharti Hospital, Meerut, Uttar Pradesh for a duration of 2 years from September 2017 to July 2019.The selected subjects were divided into two treatment arms i.e. Group 1: ulipristal acetate: 5 mg OD for 3 months and Group 2: mifepristone: 25 mg OD for 3 months. Detailed history of the patient, general physical examination and systemic examination was done followed by per abdomen examination, per speculum and per vaginal examination. A blood examination, USG (pelvis), Pap smear and endometrial biopsy was done. Subjects visited the hospital at visit 1, visit 2, visit 3, visit 4, visit 5 and visit 6 for 6 months. Results: In both the groups, maximum subjects were in the age group of 36-40 years, followed by 41-50 years. When mean PBAC score at first, second, third, fourth and fifth visit was compared statistically among ulipristal acetate and mifepristone group, it was found to be statistically significant. Uterine pain was reduced more in mifepristone group as compared to ulipristal acetate group at all the different intervals. Size was reduced more in mifepristone group as compared to ulipristal acetate group at all the different intervals. Conclusions: Authors conclude from this study that mifepristone should be preferred over ulipristal acetate for treatment of symptomatic fibroids.